Immune-mediated genetic pathways resulting in pulmonary function impairment increase lung cancer susceptibility - Linda Kachuri (Nature Portfolio, 2020)
The role of impaired lung function in lung cancer etiology is complex due to the relation of cigarette smoking to both conditions. Here, supported by Mendelian randomization analysis the authors find a link between pulmonary function impairment and lung cancer risk beyond smoking, implicating immune-related pathways